Bionic design of thin-walled tubes inspired by the vascular structure of bamboo. (May 2023) - Liu, Yansong; Qi, Yingchun; Sun, Hao; Han, Na; Zhou, Jianfei; Song, Jiafeng; Zou, Meng
Abstract: In order to improve the crashworthiness and energy absorption of thin-walled tubes, this work proposes a novel design inspired by the vascular fiber sheath flap (VF) and central through-hole characteristics of bamboo vascular bundles. The energy absorption of the bionic structure is verified by experiments and theoretical analysis. Numerical simulations are used to analyze the effect of bionic unit structure and connection settings on various crashworthiness indexes. The results show that the bionic tube achieves the optimal energy-absorbing structure when the VF unit is a semicircle and the ratio of the circle core's radius to the straight panel's length is 3:7. Further, the effect of connection between the bionic unit and the outer tube on crashworthiness is also explored, and the optimal α β -connection is obtained. Finally, both parallel fractal( PF ) and rotational fractal( RF ) approaches are introduced to improve the crashworthiness of thin-walled tubes based on the optimal structures obtained. And the crashworthiness of PF tube is better than that of the RF tube under the same level. Highlights: Bionic design is introduced to increase the energy absorption. Bionic structures are inspired by vascular bundles of bamboo. Optimal parameter and connection mode are explored, respectively. The crashworthiness under parallel fractals is better than under rotational fractals.